The Principal’s Strategy in Managing Internal Conflicts Among Educators at Islamic Vocational High School (SMK) - Istghosah Istighosah (Agrapana Media, 2025)
This study aims to analyze the strategies employed by the head of the madrasah in managing internal conflicts among educators at Sekolah Menengah Kejuruan (SMK) Al-Fattah Bojonegoro. The research utilized a qualitative field approach with data collected through in-depth interviews, participatory observation, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing with verification. The findings reveal that the types of conflicts occurring at SMK Al-Fattah include personal, role-based, and structural conflicts, which stem from differences in personality, internal policies, and organizational dynamics. The head of the madrasah implements conflict resolution strategies through consultation (musyawarah), exemplary leadership (uswah hasanah), open communication, and individual mediation. This approach is grounded in Islamic values such as shura (consultation), ‘adl (justice), and ukhuwah (brotherhood), making the resolution process not only administrative but also spiritual and educational in nature. The implementation of these strategies has led to improved workplace harmony, increased teacher motivation, and the development of a more conducive and religious organizational climate. This study emphasizes that the head of the madrasah, as an Islamic educational leader, plays a strategic role in integrating spiritual values with managerial professionalism to create a peaceful, productive, and just educational environment.